Local wisdom and national values: Quantifying the impact of project-based learning on Pancasila education outcomes - Suwartini, Sri; Sumardjoko, Bambang; Harsono, Harsono; Musiyam, Musiyam (Edelweiss Applied Science and Technology, 2025)
This study aims to evaluate the effectiveness of the Project-Based Learning (PjBL) model in enhancing the learning outcomes of Pancasila Education among Grade V students, particularly in terms of internalizing national values and fostering character development. A quantitative research design with an experimental approach was employed, where the learning outcomes of students were assessed using conventional methods before transitioning to the PjBL model. The study involved 36 Grade V students from SD Negeri Tangkisan Pos. Data analysis techniques included hypothesis testing, mean, median, and mode calculations to evaluate student progress. The results indicated that the PjBL model significantly improved student engagement and learning outcomes in Pancasila Education. Students in the PjBL group showed marked increases in both academic performance and practical application of Pancasila values, as evidenced by improved project assessments and scores. The PjBL model also fostered critical thinking, creativity, and collaboration. The study confirms that the PjBL model is an effective pedagogical approach for enhancing student learning outcomes in Pancasila Education, promoting not only academic achievement but also character development aligned with national values. The findings suggest that educators should integrate project-based learning into Pancasila Education to increase student engagement and deepen understanding of national values. Future practices should focus on providing teachers with the necessary training and resources to effectively implement PjBL in their classrooms.